Model Pemulihan Literasi dan Kesehatan Mental Anak Pengungsi Pascabencana Hidrometeorologi melalui Pembelajaran Bahasa Berbasis Trauma di Aceh - Hijran Purnama Sari Ariga; Wirdatul Isnani; Muslihin; Muhammad Rizal (CV. Global Cendekia Inti, 2026)
This study aims to develop a trauma-informed Indonesian language learning model to improve literacy skills and support the mental health recovery of refugee children following a hydrometeorological disaster in Bireuen Regency, Aceh. The study employed a Research and Development (R&D) approach, involving 48 refugee children, teachers, and volunteers. The results indicate that the developed model effectively enhances children’s engagement, participation, and self-confidence in learning. Through language activities such as reading, writing, and communication, the children began to express experiences and feelings that were previously difficult to articulate. Additionally, this model is effective in creating a safe and supportive learning environment, thereby aiding the children’s psychological recovery. Expert validation results confirm that the model falls into the “highly feasible” category for implementation. These findings confirm that integrating a trauma-informed approach into language learning can serve as an effective and adaptive strategy to support emergency education focused on children’s literacy and psychosocial needs.